2011
DOI: 10.1021/om200204y
|View full text |Cite
|
Sign up to set email alerts
|

Cooperative Effect of Silver in Copper-Catalyzed Trifluoromethylation of Aryl Iodides Using Me3SiCF3

Abstract: An effective model of cooperative effect of silver for the coppercatalyzed trifluoromethylation of activated and unactivated aryl iodides to trifluoromethylated arenes using Me 3 SiCF 3 was achieved with a broad substrate scope.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
49
0
10

Year Published

2012
2012
2018
2018

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 144 publications
(61 citation statements)
references
References 48 publications
2
49
0
10
Order By: Relevance
“…Our design of a cooperative dual Pd/Ag bimetallic catalyst [23][24][25][26][27][28] for direct difluoromethylation of aryl halides was inspired by a classical cross-coupling reaction-Sonogashira reaction 29 . It was proposed that the palladium-catalysed alkynylation of aryl halides was catalysed by a two-component catalyst system consisting of two different transition metal complexes (Pd/Cu), in which the palladium-catalysed activation of aryl halides was cooperatively coupled through a transmetalation process with the catalytic route of in situ formation cuprous acetylides in the presence of an amine.…”
Section: Resultsmentioning
confidence: 99%
“…Our design of a cooperative dual Pd/Ag bimetallic catalyst [23][24][25][26][27][28] for direct difluoromethylation of aryl halides was inspired by a classical cross-coupling reaction-Sonogashira reaction 29 . It was proposed that the palladium-catalysed alkynylation of aryl halides was catalysed by a two-component catalyst system consisting of two different transition metal complexes (Pd/Cu), in which the palladium-catalysed activation of aryl halides was cooperatively coupled through a transmetalation process with the catalytic route of in situ formation cuprous acetylides in the presence of an amine.…”
Section: Resultsmentioning
confidence: 99%
“…This decomposition product was unambiguously characterized on the basis of NMR spectroscopic methods ( 1 H, 19 F, 13 C, and correlation techniques). While the proton signal is split into a quartet caused by a 6 J(H,F) (or through space [31] ) interaction of less than 1 Hz, the 19 F signal occurs only broadened (Δ 1/2 ≈ 6 Hz).…”
Section: Articlementioning
confidence: 99%
“…[2,3,8,9] Also in the field of organic synthesis, perfluoroorgano silver compounds attract more and more attention in the conversion of acid chlorides into perfluoroorgano ketones, [10,11] in the copper-mediated trifluoromethylation of aryl halides, [12,13] in C-H fluoroalkylation of differently substituted aromatic substrates, [14][15][16] or in the conversion of diazonium salts into trifluoromethyl-substituted aromatics. [17] Earlier studies [18] revealed that in solution especially perfluoroalkylsilver derivatives undergo complex exchange equilibria involving a "neutral" species, AgR f , an "ionic" species, Ag[Ag(R f ) 2 ], and a "polymeric" form, [ 4-Dimethylaminopyridine (DMAP), additionally to its excellent catalytic activity in organic transformations, [19] exhibits positive features making among many other metal compounds silver derivatives easily crystallizable.…”
Section: Introductionmentioning
confidence: 99%
“…Third, AgCF 3 is readily synthetically accessible (although its reactivity with organic substrates had not previously been explored extensively). 20 …”
Section: Part 2: Aryl Trifluoromethylation Using Agcf3mentioning
confidence: 99%
“…For example, several reports have shown that Ag salts serve as promoters for the Cu-catalyzed trifluoromethylation of aryl iodides. 20b,31 The role of Ag has been proposed to involve mediating transmetalation of CF 3 − from Si (in TMSCF 3 ) to Cu. 17b However, the current results (along with those in Part 2 of this Account) suggest that the role of Ag may be to generate CF 3 • in these transformations.…”
Section: Part 3 Cu-catalyzed Aryl Trifluoromethylation With Cf3•mentioning
confidence: 99%